2023
DOI: 10.1002/jhbp.1321
|View full text |Cite
|
Sign up to set email alerts
|

Comparing endoscopic ultrasound‐guided antegrade treatment and balloon endoscopy‐assisted endoscopic retrograde cholangiopancreatography in the management of bile duct stones in patients with surgically altered anatomy: A retrospective cohort study

Abstract: BackgroundEndoscopic ultrasound‐guided antegrade treatment (EUS‐AG) and balloon endoscopy‐assisted endoscopic retrograde cholangiopancreatography (BE‐ERCP) have emerged as useful procedures for managing bile duct stones (BDS) in patients with surgically altered anatomy. However, the comparison between these two procedures has not been well studied.The aim of our study was to compare the clinical outcomes of EUS‐AG and BE‐ERCP for managing BDS in patients with surgically altered anatomy.MethodsThe database was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Using the search strategy above, 33 studies were screened, duplicates were removed, and 3 were included ( Fig. 1 ) [ 12 - 14 ]. All included studies were observational.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using the search strategy above, 33 studies were screened, duplicates were removed, and 3 were included ( Fig. 1 ) [ 12 - 14 ]. All included studies were observational.…”
Section: Resultsmentioning
confidence: 99%
“…The core of our findings indicates that there is no significant difference in the technical and clinical success rates between EUS-AG and BE-ERCP. This outcome suggests that both techniques are equally viable options for endoscopic intervention in RYGB, allowing for flexibility in clinical decision-making based on the practitioner’s expertise and the specific circumstances of each case [ 12 - 14 ]. Itoi et al , in a recent case series of patients with surgically altered anatomy and choledocholithiasis, report a technical success rate of 60% with the EUS-AG technique [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…This outcome suggests that both techniques are equally viable options for endoscopic intervention in RYGB, allowing for exibility in clinical decision-making based on the practitioner's expertise and the speci c circumstances of each case. [12][13][14] Itoi et al report a technical success rate of 60% with EUS-AG technique in a recent case series of patients with surgically altered anatomy and choledocholithiasis. 18 Iwashita et al also reported the results of a prospective study of antegrade stenting in twenty patients with surgically altered anatomy.…”
Section: Discussionmentioning
confidence: 99%
“…Using the search strategy above, 33 studies were screened, duplicates were removed, and three were included. (Figure 1) [12][13][14] All included studies were observational. 795 patients were included, which also corresponded to the total number of procedures performed including EUS-AG and BE-ERCP.…”
Section: Systematic Reviewmentioning
confidence: 99%
“…The rate of complete stone removal raised up to 90% by rescue PTBD or EUS-HGS after failed BE-ERCP in this study. EUS-HGS is a potential salvage treatment for hepatolithiasis in patients with SAA [ 15 , 29 ], and there are some case reports for successful removal of hepatolithiasis using HGS route [ 30 ]. Furthermore, direct cholangioscopy through the HGS route and subsequent electrohydraulic lithotripsy under a direct visualization could be an option for large stones [ 31 ].…”
Section: Discussionmentioning
confidence: 99%